WATER BALANCE IN JAPANESE MALE COLLEGE ARTISTIC GYMNASTS DURING TRAINING - HIGASHIONNA, Akiyo; FUJITA, Chisa; YOSHIDA, Goichiro; MURATA, Kensuke; YOSHITAKE, Yutaka; YOSHIDA, Shiho; KITAGAWA, Junichi; TANI, Satoki (Japanese Journal of Physiological Anthropology, 2023)
This study assessed differences of water balance by season for a group of Japanese college male artistic gymnasts during training. The seasonal differences in water balance were evaluated using ANCOVA with energy expenditure as the covariate. After adjusting for the influence of energy expenditure, the amount of sweating, sweating rate, amount of water intake, and water intake rate varied significantly by season, with the highest values recognized in summer, followed by spring and then winter. Rehydration rate was recorded as 23% for spring, 35% for summer, and 5% for winter. Although the results of specific team of artistic gymnastics, these results suggest that water intake is essential before, during and after training in any season.